Pengaruh Perbedaan Jumlah Katalis terhadap Angka Yield pada Proses Pembuatan Biodiesel dari Minyak Goreng Sisa Menggunakan Pemanas Double Jacket - Suherman, Suherman; abdullah, ilmi; Sabri, Muhammad; Silitonga, Arridina Susan; Suroso, Bekti (Jurnal Rekayasa Mesin, 2022)
Biodiesel is biodegradable and non-toxic and has a low carbon content, high lubricity, and Biodiesel is biodegradable and non-toxic and has a low carbon content, high lubricity, and higher ash point than diesel. The purpose of this study was to obtain data on the physicochemical properties of biodiesel from waste cooking oil (WCO) produced with different amounts of catalyst in the transesterification process. Methods This research carried out a two-step process: (1) esterification with an acid catalyst (H2SO4) and (2) transesterification with an alkali catalyst (KOH). The remaining frying oil is degummed by adding 2% H3PO4. Furthermore, the esterification process was carried out by adding 2% (v/v) H2SO4 at 800 rpm for 90 minutes. The transesterification process using an alkaline catalyst (KOH) was varied from 0.7-1.5% at a temperature of 60 oC with a rotation of 800 rpm and a time of 90 minutes. In the ester/transesterification process, the ratio of methanol: oil is 1:2 (v/v). The biofuels are then tested for cetane number, flash point, density, viscosity, calorific value, and others. The results showed that the amount of wet catalyst (KOH) in the transesterification process gave a difference in the yield of WCO oil. The optimum value was obtained at the amount of 1% KOH catalyst, which was 85%.